Efektivitas Pendayagunaan Zakat Produktif Pada Pemberdayaan Ekonomi Di Baznas Provinsi Jawa Timur - Indriati, Cicik; Fahrullah, (Jurnal Ekonomika dan Bisnis Islam, 2019)
This research is a qualitative descriptive study which aims to determine the effectiveness of the utilization of productive zakat on economic empowerment of mustahik. The data collection technique uses observation, interviews, and documentation. From the research results it can be concluded that the concept of productive zakat utilization on mustahik economic empowerment carried out by BAZNAS East Java Province was poured into several programs, namely in the form of providing business capital assistance both individually and in groups, providing work skills training, and providing work tools. As for the effectiveness indicators using the theory from Ni Wayan Budiani, namely: the accuracy of program targets, program socialization, program objectives, and program monitoring. The results of this study indicate that the indicators of the accuracy of program targets and have been effective. As for indicators of program socialization, program monitoring, and program objectives can be said to be ineffective.